Melhoria da robustez e eficiência em acionamentos de motores de indução trifásicos combinando as técnicas IFOC, LMC e MRAC - Jung, Clecio (2020)
Indirect Field Oriented Control (IFOC) provides a satisfactory dynamic response for PWMinverters driving three-phase induction motors, and this is a solution widely used in the industry.As a large part of the electric energy is destined to drive motors, the concern with energyefficiency has led to research aiming to reduce the energy consumption of this kind of drivesystem. In this work, a Loss Model-based Control (LMC) was implemented, and 41% reductionin power consumption of the drive system was observed experimentally in comparison withconventional IFOC controller, both operating at nominal speed and without external mechanicalload. However, the LMC technique is sensitive to the variation of the motor parameters, and tominimize this effect, an MRAC algorithm based on active and reactive power is used to estimatein real-time the parameters of the stator and rotor bandwidth (γandη), coefficients that varywidely with temperature, and thus correct their values in real-time in the operation of the LMCsystem. This proposed new strategy was called Adaptive LMC (ALMC) and experimentally wasobserved energy savings of up to 12.5% compared to the conventional LMC method, for anincrease in engine temperature of approximately23◦C. Some modifications are also includedin the IFOC controller, such as the use of a reference pre-filter and derivative term in thespeed controller, to improve the dynamic response and decrease the maximum deviation whenload input occurs. Also, observing that the IFOC controller is sensitive to variations in theηcoefficient, its estimated value is used to compensate for possible variations in the determinationof the rotational flow reference, and thus increase the overall robustness of the control system.